School money trials : the legal pursuit of educational adequacy - West, Martin R.; Peterson, Paul E. (Washington, D.C. : Brookings Institution Press, 2007)
Adequacy lawsuits have, with little fanfare, emerged as a major alternative strategy in the pursuit of improved public education in the United States. Plaintiffs allege insufficient resources to provide students with the quality of education promised in their state's constitution, hoping the courts will step in and order the state to increase funding levels. Since 1985, more than thirty states have faced such suits. How pervasive--and effective--is this trend? What are its ramifications, in local school districts and on a broader scale? This important new book addresses those questions. In Sch.
The adequacy lawsuit : a critical appraisal / Martin R. West and Paul E. Peterson -- Adding adequacy to equity / Richard Briffault -- Reinterpreting the education clauses in state constitutions / John C. Eastman -- The alchemy of "costing out" an adequate education / Eric A. Hanushek -- The politicization of the school finance legal process / Matthew G. Sringer and James W. Guthrie -- Is teacher pay "adequate"? / Michael Podgursky -- Adequacy judgments and school reform / Frederick M. Hess -- The non-implementation of New York's adequacy judgment / Joe Williams -- The impact of school finance judgments on state fiscal policy / Christopher Berry -- Adequacy, accountability, and no child left behind act / Andrew Rudalevige -- Adequacy litigation in an era of accountability / Michael Heise -- The winning defense in Massachusetts / Robert M. Costrell -- The uncertain future of adequacy remedies / Kenneth W. Starr -- Adequacy litigation and the separation of powers / Joshua Dunn and Martha Derthick.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Educational equalization -- Law and legislation -- United States; Educational accountability -- Law and legislation -- United States; Discrimination in education -- Law and legislation -- United States; Education -- Finance -- Law and legislation -- United States -- States; Education -- United States -- Finance; LAW -- Administrative Law & Regulatory Practice; EDUCATION -- Educational Policy & Reform -- General; Discrimination in education -- Law and legislation; Education -- Finance; Education -- Finance -- Law and legislation -- U.S. states; Educational accountability -- Law and legislation; Educational equalization -- Law and legislation; United States